Genetic variability and association among colour and white seedless genotypes of grape (Vitis vinifera) - SANIYA, SANIYA; KANWAR, JYOTI; NARUKA, I S; SINGH, P P (The Indian Journal of Agricultural Sciences, 2018)
Twenty three genotypes (11 colour seedless and 12 white seedless) of grape (Vitis vinifera L.) were investigated during 2015-16 to evaluate qualitative and quantitative traits to explore its existing gene pool and identify the selection indices important for grapevine improvement. Traits like acidity, days to ripening, heat unit requirement, total sugars, number of berries per bunch and TSS had least variation among the coefficients both at phenotypic and genotypic level. High estimates of heritability (broad sense) and genetic advance were observed for some traits signifying high potential for improvement of grape through selection and are governed by additive gene action. Highest heritability was recorded for acidity (99.95) and low for days (33.57) taken to 50% panicle appearance. Correlation coefficients at phenotypic and genotypic level envisaged that fruit yield per vine was having significant and positive correlation with number of bunch and number of fruitful canes. These are the most important characters contributing towards fruit yield and can be strategically used to improve the yield of grape.